Paramaribo revisited. The notion of the coherent wooden city (Bulletin KNOB, 2009)
The historical wooden city of Paramaribo was discovered and described by M.D. Ozinga, J.L. Volders and C.L. Temminck Groll in the sixties of the previous century. In their publications the three authors give different perspectives. In Surinaamse bouwkunst Volders describes Paramaribo as a coherent wooden city, in which three centuries’ building from small to large forms a stylistic and typological family. For this purpose he introduced the term ‘Surinam building tradition’. In Proeve van een monumentenlijst voor Suriname Ozinga chiefly describes the eighteenth-century colonial government buildings and aristocrats’ houses. Thus he presents Paramaribo as a Dutch colonial monument unique in South America for its intactness and age. In De Architectuur van Suriname 1667-1930 Temminck Groll gives a complete and differentiating image of historical Paramaribo through his accurate description of a large number of buildings and describes the transformations in architecture and urban planning.Their publications from the sixties and seventies formed the basis of the fact that Paramaribo was placed on the UNESCO World Heritage List in 2002.The various visions of the authors are to be traced back to the nomination file, where they have merged into one single slogan: Paramaribo is a coherent, eighteenth-century wooden city with a Dutch colonial past.The image Temminck Groll, Ozinga and Volders came across, however, was a random picture in the permanent transformation of the city: Paramaribo is no longer a coherent wooden city. However, the dynamic interweaving of heterogeneous cultural patterns, which led to the ‘Surinam building tradition’, is still taking place and has resulted in new interpretations of city and architecture. The permanent historical structure is not just constituted by the monumental buildings, but particularly by the large multifunctional blocks of buildings, the informal building lines and the landscape orientation, which even in a changing city form the historical framework. For that reason the description of the city centre of Paramaribo should be brought up to date.The publications of Temminck Groll, Ozinga and Volders are important sources for this.